Now you see me: diversity, CEO education, and bank performance in the UK - Mohamed Elsharkawy; Audrey S. Paterson; Mohamed Sherif (Investment Management & Financial Innovations, 2018)
This paper investigates the impact of board diversity and CEO educational background on bank performance. Based on a sample of 54 UK publicly listed banks over the period 2005–2015, we examine the relationship of both static and dynamic modelling frameworks, which controls for individual specific effects and potential sources of endogeneity. The study reports a positive but insignificant relationship between CEO education and bank performance, and a positive significant association between gender diversity and bank performance. It further denotes a negative and significant impact of nationality diversity on bank performance. Our findings provide empirical support for the significance of the association between board diversity and firm performance. Our study also provides support for theories concerned with how corporate governance differs in financial institutions.